New approach of Samak clay usage for halal industry requirement - Kassim, Norrahimah; Hashim, Puziah; Mat Hashim, Dzulkifly; Jol, Hamdan (Elsevier, 2014)
Halal food, pharmaceutical, cosmetic and personal care products are considered najis if they are either contaminated or are in direct contact with najis al-mughallazah (extreme najis). Cleansing of extreme najis require the use of samak clay or soil. Thus, in compliance with the halal industry requirements, a study of samak clay as the potential industrial Islamic cleansing application was conducted. Heavy metal contaminants and clay properties such as pH, particle size distribution (PSD) and moisture content were determined. The study on the clay properties of samak will be able to facilitate the acceptance of it in the area of Islamic cleansing of extreme najis throughout the halal supply chain of foods, pharmaceutical, cosmetics and other halal industries. This new approach of samak clay usage is commercially viable for those related halal industries as it is conveniently and economically produced. Samak clay as a commercial product that meets the standard halal requirements of quality and safety will further enhance consumer confidence.